Building Digital Capability in Startups: The Roles of Technology Orientation and Innovation-Oriented Leadership - Christin Susilowati (CV. Sakura Digital Nusantara, 2026)
Purpose: This study examines the roles of technology orientation and innovation-oriented leadership in shaping digital capability in startups. It specifically positions digital capability as a primary strategic outcome and explores how internal strategic factors contribute to its development. Design/methodology/approach: This study uses a quantitative explanatory design. Data were collected from 105 founders or co-founders of digital startups through a structured questionnaire. The data were analyzed using PLS-SEM with SmartPLS 3 and bootstrapping of 5,000 subsamples. Business age and market segmentation were included as control variables. Finding/Results – The results show that technology orientation has a significant positive effect on digital capability. Innovation-oriented leadership also significantly influences digital capability and emerges as the strongest direct predictor. In addition, the interaction between technology orientation and innovation-oriented leadership has the largest effect, indicating a strong synergistic relationship in strengthening digital capability. Market segmentation significantly affects digital capability, while business age does not show a significant effect. Originality/Value – This study highlights digital capability as a key strategic outcome in startup research. It also shows that the combined effect of technology orientation and innovation-oriented leadership is more important than their separate effects. The findings enrich the literature on startups by offering evidence from emerging digital businesses and by showing the relevance of market segmentation in explaining digital capability.